The Implementation of Educational Supervision at SMP Negeri 2 Banyuke Hulu - Julia Larasanti; Marinu Waruwu; Halida; Eny Enawaty (Bulletin of Science Education, 2024)
Educational supervision is a crucial component in efforts to improve the quality of education. This study aims to analyze the implementation of educational supervision at SMP Negeri 2 Banyuke Hulu, focusing on supervision practices, teacher perceptions, challenges, effectiveness, and development strategies. Using a qualitative approach with a case study design, this research involved in-depth interviews, participant observation, and document analysis. The results show that despite facing challenges in terms of limited resources, the school has successfully implemented a collaborative supervision model that is effective in improving teacher competence and the quality of learning. Technology integration and data-driven approaches have become key strategies in optimizing the supervision process. Theoretical and practical implications of these findings are discussed, along with recommendations for developing a more adaptive and contextual supervision system. This research contributes to a more comprehensive understanding of the dynamics of educational supervision in the context of junior high schools with limited resources